IDENTIFICATION OF FACTORS INHIBITING CAREER PLANNING IN GRADE XII STUDENTS OF SMK N 1 TEMPEL WITH LOW ECONOMIC BACKGROUND - Purnomo, Ipung (Program Studi Bimbingan dan Konseling FKIP UMSU, 2026)
This study explores career planning among vocational high school students from low-income families and the factors inhibiting it. Data from five twelfth-grade students (KIP recipients) and two counselors were collected through interviews and document analysis. Findings show students’ career planning is immature, with unclear goals and uncertainty about post-graduation plans. Barriers include economic constraints, low self-efficacy, limited parental support, and underutilized school guidance services. Continuous and structured guidance is needed to foster realistic, self-potential-based career planning.